PROGRAM EVALUATION INVOLVEMENT INDONESIAN NATIONAL ARMED FORCES (TNI) ON MISSION UNITED NATIONS PEACEKEEPING OPERATIONS (UNPKO) - I Gede Sumertha KY; Moch Asmawi; Khasan Gunawan (IJHCM (International Journal of Human Capital Management), 2017)
Abstract This research is constructed in order to study and to evaluate involvement TNI on mission United Nations Peacekeeping Operations (UNPKO) in Lebanon program FY 2014-2015 due to achieve vision 4000 Peacekeepers. The CIPP model is using on apply qualitative method for the research with consist of four evaluation components: (1) context; (2) input; (3) process; (4) product. The mechanism collecting data were collected through interviews, observations, questionnaires and documentation study. There are three levels of evaluation for judgment each aspect: low, moderate, and high. The summarized results and figured into case-order effect matrix was figure out of the categorization.The results of this research indicates that TNI involvement in mission UNPKO Lebanon, aspire to increase the number of peacekeepers up to 4.000 personnel in the category Ã¢â‚¬Å“highÃ¢â‚¬Â, but still have some minor additional improvement especially on coordination among stake holders. This is because the Results of Context Evaluation has a category of "high" with a scale of assessment "many" (75.3%); the Results of Input Evaluation has a category of "high" with a scale of assessment "moderate" (60.6%); the Results of Process Evaluation has a category of "high" with a scale of assessment "moderate" (65.3%) and the Results of Product Evaluation has a category of "high" with a scale of assessment "moderate" (63.3% ). Keywords: evaluation, program, vision 4.000,TNI, UNPKO and CIPP.